2005
DOI: 10.1038/sj.leu.2403690
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis in Hodgkin's lymphoma: a morphometric approach in 286 patients with prognostic implications

Abstract: The significance of angiogenesis in Hodgkin's lymphoma (HL) is not well defined. The aim of this study was to evaluate various morphometric characteristics of microvessels in lymph node sections of 286 patients with HL at diagnosis and investigate their relationship with clinicopathologic parameters and prognosis. Microvessel density (MVD), total vascular area (TVA) and several size-and shape-related microvascular parameters were quantitated -after anti-CD34 immunohistochemical staining -in the region of most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 32 publications
(36 reference statements)
2
34
0
4
Order By: Relevance
“…When tested in a multivariate analysis against age and low s-albumin, the most powerful prognostic factors, the microvessel count was not statistically significantly related to PFS (P ¼ 0.10), probably due to the very strong influence of age on prognosis. The observed correlations between high number of microvessels and high age on the one hand (Table 1) and worse PFS, on the other hand ( Figure 2) are in line with the recent study by Korkolopoulou et al 1 However, in that study a morphometric approach was used where they investigated different features of the microvessels. 1 It might be speculated that the higher number of microvessels in elderly patients points towards a biological difference between HL in younger and older patients.…”
Section: Angiogenesis and Mast Cells In Hodgkin Lymphomasupporting
confidence: 62%
See 1 more Smart Citation
“…When tested in a multivariate analysis against age and low s-albumin, the most powerful prognostic factors, the microvessel count was not statistically significantly related to PFS (P ¼ 0.10), probably due to the very strong influence of age on prognosis. The observed correlations between high number of microvessels and high age on the one hand (Table 1) and worse PFS, on the other hand ( Figure 2) are in line with the recent study by Korkolopoulou et al 1 However, in that study a morphometric approach was used where they investigated different features of the microvessels. 1 It might be speculated that the higher number of microvessels in elderly patients points towards a biological difference between HL in younger and older patients.…”
Section: Angiogenesis and Mast Cells In Hodgkin Lymphomasupporting
confidence: 62%
“…It has recently been reported that angiogenesis correlates to poor prognosis in HL. 1 We have previously reported that HL patients with many mast cells in their tumour tissue have a worse prognosis. 2 Mast cells produce functionally active CD30 ligand (CD30L) and the poorer prognosis has been proposed to be caused by a stimulation of HRS by CD30L.…”
Section: Angiogenesis and Mast Cells In Hodgkin Lymphomamentioning
confidence: 99%
“…26,27 In this study, we have shown that the more aggressive SOX11-positive MCL xenografts were enriched in angiogenic gene signatures and displayed much larger microvascular density areas than their SOX11-negative counterparts, concurring with other observations that an increased MVD correlates with disease progression in lymphoid neoplasms. 28,29 We therefore postulated that SOX11-positive MCL cells could promote a pronounced vasculature development and obtain an increased and deregulated blood supply that may contribute to their aggressive progression.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found a correlation between VEGF expression and prognostic factors for nonHodgkin's human lymphomas, concluding that VEGF immunostaining may be an effective method to evaluate the biological behavior of lymphomas (HAZAR et al, 2003;KORKOLOPOULOU et al, 2005). …”
Section: Discussionmentioning
confidence: 99%